Calculation of the Total Solar Radiation for City of Nasiriyah per Month during the Year (University of Thi-Qar Journal for Engineering Sciences, 2022)
Solar energy is the sun-emitting light and heat that man has used a wide variety of developing technologies since ancient times techniques for solar energy include the use of solar thermal energy, whether for direct thermal heating or as part of the process of mechanical conversion for movement or electric energy, or the use of photovoltaic panels for electricity through photovoltaic panels.Alongside secondary energy sources like wind energy, wave energy, hydroelectric power and biomass, most of the renewables accessible on the Earth's surface are attributable to solar radiation. It should be pointed out that in our lives just a little of the solar energy accessible has been utilized Solar energy produced by heat engines or photovoltaic converters produces electricity .electricity only human genius regulates its applications after solar energy is transformed into electric power heating and cooling systems in architectural designs depending on the exploitation of solar energy are among the applications created utilizing solar energy. Drinking water, sunshine, water heating, solar cooking and heating for industry uses, during distillation and disinfection .In general, solar technologies are described as passive solar energy systems or passive solar energy systems depending on how sunlight is used, processed and dispersed. The use of photovoltaic panels and a solar thermal collector with mechanical and electrical equipment for converting sunlight into other usable energy sources are technologies that rely auf the use of positive solar energy .this is done by using passive solar energy to direct a structure to the sun, use materials with the corresponding thermal mass or light disseminating characteristics and create spaces , which circulate the air naturally. In this research, the total solar energy calculations for the city of "Nasiriya" are found from the total direct and dispersed energy as well as reflected through its own laws, and the geographical location and the angles of inclination of solar radiation and the angles of inclination of the receiving solar complex to the sun for three times during a day in every month over the course of The year is in addition to the ground reflectivity factor, and some other factors such as clouds, humidity, dust and smoke have been excluded from the calculations.